Rural structures in the tropics : design and development - Mrema, Geoffrey C.; Food and Agriculture Organization of the United Nations; Technical Centre for Agricultural and Rural Cooperation (Ede, Netherlands) (Rome : Food and Agriculture Organization of the United Nations, 2011)
"This book is an effort by FAO to compile an up-to-date, comprehensive text on rural structures and services in the tropics, focusing on structures for small- to medium-scale farms and, to some extent, village-scale agricultural infrastructure. The earlier edition, entitled Farm structures in tropical climates: a textbook for structural engineering and design, published in 1986, has been used for over two decades as a standard textbook for teaching undergraduate and postgraduate courses on rural structures and services in universities throughout sub-Saharan Africa. This second edition will help to improve teaching - at all educational levels - on the subject of rural buildings in developing countries in the tropics and it will assist professionals currently engaged in providing technical advice on rural structures and services, from either agricultural extension departments or non-governmental rural development organizations. This book will also provide technical guidance in the context of disaster recovery and rehabilitation, for rebuilding the sound rural structures and related services that are key to development and economic sustainability. While this book is intended primarily for teaching university - and college-level agricultural engineering students about rural structures and services, resources might be made available to produced textbooks based on this material for teaching at other educational levels. Although parts of the background material relate specifically to East and Southeast Africa, the book's principles apply to the whole of tropical Africa, Latin America and South Asia because, while building traditions may vary, the available materials are similar"--P. [4] of cover.
"CTA"--Cover.
"Based on the FAO publication Farm structures in tropical climates"--P. xi.
Keywords: Farm buildings; Farm buildings; Farm layout; Farm layout